Pesticide Labeling: Ingredient Statements - Frederick M. Fishel (EDIS, 2006)
This guide explains how pesticide ingredient statements are presented on the pesticide label for products' active and inert ingredients. Examples of various types of pesticides are provided. This document is PI-111, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.